Contemporary Management of Blunt Thoracic Aortic Injury: Results of an EAST, AAST and SVS survey by the Aortic Trauma Foundation - DeSoucy, Erik; Loja, Melissa; Dubose, Joseph J; Estrera, Anthony; Starnes, Ben; Azzizadeh, Ali (Journal of Endovascular Resuscitation and Trauma Management, 2017)
Objective: To determine contemporary management practices for blunt thoracic aortic injury (BTAI) among trauma and vascular surgeons. Methods: A survey of Eastern Association for the Surgery of Trauma, American Association for the Surgery of Trauma and Society of Vascular Surgeons (SVS) membership regarding BTAI care was conducted. Results: 404 respondents included trauma (52.5%), vascular (42.6%) and other specialty providers (4.5%) primarily from North American (90.6%) academic teaching institutions (71.0%) / American College of Surgeons Level I trauma centers (58.9%). Most respondents managed one to fi ve BTAIs annually (71.6%). Preferred diagnostic modality was computed tomographic angiography (CTA) (99.8%), after which respondents stated they preferred to utilize personal knowledge of the literature and experience (50.5%), the SVS guidelines (27.4%) or institution specifi c guidelines (12.8%) to guide subsequent management. Respondents primarily agreed on the treatment of intimal tears (SVS G1) with medical management. For intramural hematoma (SVS G2), management choice was divided between medical 46.6%) and thoracic endovascular aortic repair (TEVAR) (46.3%). Both groups defi ned TEVAR as treatment of choice for hemodynamically stable patients with pseudoaneurysm (SVS G3) (93.5%) and rupture (SVS G4) (82.2%), although a greater number of trauma surgeons preferred open repair (20.4%) than vascular counterparts (4.1%) in stable G4 patients. Preferred medical management goals varied between mean arterial pressure (37.3%) and systolic blood pressure (62.3%) targets. Preferences also varied in adjuncts for open repair (left heart bypass 56.5%; clamp and sew 46.1%; cerebrospinal fl uid (CSF) drainage 48.5%) and TEVAR (percutaneous puncture for arterial access 58.4%; open vascular exposure 65.5%, intravascular ultrasound 36.1%, CSF drainage 28.9%). Outpatient follow-up timing (2 weeks 37.0%, 1 month 37.2%) and initial type (clinical exam 36.6%, CTA 48.3%) also varied. Conclusions: The survey of trauma and vascular surgeons illustrates controversy regarding SVS G2 treatment, surgical adjuncts and follow-up. Additional study is required to identify optimal BTAI management.